Pemikiran kritis dan amalannya dalam masyarakat India berpendidikan Tamil di Malaysia berpandukan teks Tirukkuṟaḷ / Kartheges Ponniah - Kartheges, Ponniah (2017)
Critical thinking is a thought domain that helps increase understanding, clarity and an ability to use information effectively. In addition, it enables one to make rational judgments or reasoning. Tirukkural is a text based on human life that serves as guidance. This study examined the critical thinking concept and its practice among the Tamil-educated Indians in Malaysia. A mixed method design that combined both quantitative and qualitative elements was used in this study. A total of 400 respondents that was divided into 200 males and 200 females aged 21 years and above from the Indian community was selected through clustered random sampling method. The instrument used in this study was a questionnaire developed by the researcher with a reliability (r = 0.94). The descriptive study using grading method showed that the application of the concept of cause and effect portrayed an excellent level of 5.0%, very good level of 24.7% and 43.0% was within a good level while 21.3% showed medium level of application. In addition, 6.0% was still weak in the application of this idea. The application level of problem-solving skills denoted only 7.5 % on excellent level, while 23.5% portrayed a very good level and 38.0% showed a good level of with another 24.0% with a medium level of application of the problem solving skills in their daily lives. Inferential analysis showed that age, education level and profession affect the level of critical thinking and practice significantly. However, gender did not show any significant difference in the practice of critical thinking among the Tamil-educated Indian community in Malaysia. Therefore, gender did not influence the practice of critical thinking skills advocated by Tiruvaḷḷuvar. The findings of the quantitative analysis were consistent with the views and input provided by the informants interviewed. The results of this study proved that the Tamil-educated Indian community in Malaysia has the ability to think critically as suggested by Tiruvaḷḷuvar. However, the level of critical thinking is influenced by various factors such as age, education level and profession. To conclude, critical thinking skills advocated by Tiruvaḷḷuvar are still being practised although the world has stepped into the era of information technology. Thus, Thirukurral marks its relevance in everyday life despite its declining appreciation among youths today.